Partisanship and the Gender Pay Gap in Local Government - Alonso, Jose Manuel; Andrews, Rhys (Governance (Oxford), 2025)
ABSTRACT Partisanship may play a part in shaping gender equality within public organizations, especially in local governments, which are often subject to direct political control. Using a Regression Discontinuity (RD) Design, we examine the influence of partisanship on gender equality within government by analyzing whether right‐wing party control is related to the gender pay gap among all employees in English local governments. We also investigate whether it is related to gender representation among the senior managers in those governments. Our RD estimates reveal that right‐wing controlled local governments have a larger gender pay gap and fewer women in senior management than in governments controlled by other political parties.